Periodontitis as early detection of diabetes mellitus: a literature review - Ade Indah Pratiwi (DiscoverSys Inc., 2020)
Background: Diabetes mellitus (DM) is a growing health problem and its prevalence is dramatically increasing, particularly in Indonesia. It can affect every organ in the body, and one of the oral manifestations is periodontitis characterized by the loss of tissue attachment. This review aims to identify further the periodontitis as early detection of diabetes mellitusMethods: A review of relevant literature was performed to elaborate on periodontitis involvement in diabetes mellitus. A total of 25 qualified published literature of all years were collected from several electronic database and manual search and included in this review.Results: On average, patients with periodontitis showed higher glycated haemoglobin (HbA1c) plasma levels compared with individuals without periodontitis. Diabetes and periodontitis are complex chronic diseases with an established bidirectional relationship. There is long-established evidence that hyperglycemia in diabetes is associated with adverse periodontal outcomes. Here, we show that periodontitis is an early sign of diabetes mellitus and may, therefore, serve as a valuable risk indicator. A dentist who got patient with periodontitis is a suitable location for screening for diabetes by a simple finger stick and validated HbA1c dry spot analysis.Conclusion: Literature from a different type of study concluded that periodontitis is one of the oral manifestations that could be used as early detection in diabetes mellitus